Análise por geoprocessamento das unidades de paisagem nos municípios de Rosário, Axixá e Icatu – MA - Lima, Deuzanir da Conceição Amorim (2020)
The landscape in the geographical context plays a fundamental role in the distribution of populations and in the use of space. Consequently, studies that seek to understand its units have become increasingly indispensable, especially for managing the sustainable use of the environment. The municipalities of Rosario, Axixá and Icatu together form the right shore of São José Bay where three important rivers flow, among which the Itapecuru River stands out for its size as well as its socioeconomic importance as it is the main source of water supply to the capital of Maranhão and other surrounding municipalities. In addition, these three coastal municipalities, included in the São Luís metropolitan region and which are also part of the Upaon Açu- Miritiba-Alto Preguiças APA, have extremely important physical geographical aspects for the coastal zone of the state, still lacking in of update’s studies and mapping. In view of this lack, this research aimed to make an analysis of landscape units through the use of geoprocessing, using the technique of map algebra. From the use of conventional methodologies, it was indispensable to develop an appropriate methodological proposal that met the expectation of the work when the clarity and objectivity of the results. Through the methodology, then developed was made the Geological, Geomorphological, Vegetation and Slope characterization considering the relation of the environment with the proximity of the coastline. After that, the information plans corresponding to each geographic aspect were overlapped by applying map algebra using the ArcGis 10.2 program, from which a total of 10 Landscape Units that were discussed according to their typological aspects and their use and coverage. In this sense, the developed methodology was very efficient regarding the clarity in the process of crossing the data in the algebra and its representations in the final map. The results indicated by the methodology could be validated through the CPRM geology shape considered more current than the IBGE that had been used in algebra and through the field truth.